UJI EFEKTIFITAS PENANGGULANGAN LARVA KUMBANG TANDUK (Oryctes rhinoceros) MENGGUNAKAN KIMIAWI BERBAHAN AKTIF SIPERMETRIN DAN JAMUR METARHIZIUM ANISOPLIAE - Sulthon Parinduri; Ahmad Saleh; Aderian Suhanda (Institut Teknologi Sawit Indonesia, 2017)
Research done in the area of campus of the STIP-AP FIELD. This research aims to reduce breeding populations of pest beetles Horn o. rhinoceros. the design used i.e. random design group (RAK). This research as a simple observation and expected to be material information in pest control beetle horns and make the kind of alternative environmentally friendly as well as being consideration for the company's plantations in determining method of pest control beetle horns the o. rhinoceros is most effective in a palm plantation. The observations done 2 days long with 14 days observation. research include mortality of Larval mortality oryctes rhinoceros with the chemical insecticide applications made using biological pest control and Sipermetrin active fungus Metarhizium anisopliae.